Pengaruh ekstrakurikuler kepramukaan terhadap kedisiplinan peserta didik sekolah dasar di Kecamatan Laweyan - Nugraheni, Fauziah; Riyadi, Riyadi; Ardiansyah, Roy (Universitas Sebelas Maret, 2023)
One of the factors that affect student discipline is the habituation to be disciplined. Schools can apply or instill discipline habituation through extracurricular activities. Scout extracurricular is one of the activities that can support character education and the formation of children's discipline. Scouts have a very important role in the process of character building, values, discipline and responsibility in accordance with article 3 of Law No. 20 of 2003 concerning the National Education System (National Education System). The research was carried out at SDN Mangkubumen Kidul No 16 Surakarta as an instrument trial, SDN Mangkubumen Lor No 15 Surakarta, SDN Bratan 2, and SDN Bratan 3 in January 2023 – January 2024. The research approach used is a quantitative approach in the form of an associative problem formulation of causal relationships. The sampling technique in this study uses probability sampling, namely Cluster random sampling. The data collection technique uses a Likert scale questionnaire with closed statements. The instrument validity test in this study uses content validity with the Gregory formula and reliability test using the Alpha Cronbach formula. The normality test in this study used the Kolmogorov-Smirnov test and the linearity test using the test of linearity. The hypothesis testing techniques used in this study are simple regression analysis including correlation analysis, meaningfulness test, and coefficient of determination. The result of the correlation coefficient between extracurricular scouting and student discipline is 0.635 and is classified as a strong correlation. The results of the significance test obtained > results so that it can be concluded that there is a positive and significant influence between extracurricular scouting on student discipline and the contribution of scouting extracurricular influence on student discipline by 40.3% while 59.7% is influenced by other factors that were not studied in this study.